ISTIKHDAM CHATGPT WA GOOGLE TRANSLATE FI TARJAMATI KITAB TA’LIM AL MUTA’ALLIM - Ilman Paris; Hairul Hidayah (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
The translation of Arabic texts in the contemporary era faces increasingly complex challenges alongside the development of science, technology, and global socio-cultural dynamics. These challenges are not only linguistic in nature, but also cultural, ideological, methodological, and technological. This research aims to analyze the accuracy of classical Arabic text translation in the book Ta'lim al-Muta'allim through ChatGPT and Google Translate. This study was conducted at STIT Darussalamin NW Praya, Central Lombok, using a descriptive qualitative approach. Data were obtained through analysis of translation results from both platforms on selected texts, as well as through interviews with students who use both tools in learning activities, and interviews with lecturers who frequently use these platforms. The research findings indicate that Google Translate excels in speed and ease of access, but tends to produce literal translations that are less contextually accurate. Meanwhile, ChatGPT is capable of providing more contextual and communicative translations, although it requires additional instructions from users in directing the desired results. This research concludes that the use of ChatGPT has higher accuracy as a supporting tool for translating classical Arabic texts, but still requires validation from language experts or supervising lecturers.